Convergence of Intelligent Data Acquisition and Advanced Computing Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a collection of published articles from the Sensors Special Issue on "Convergence of Intelligent Data Acquisition and Advanced Computing Systems". It includes extended versions of the conference contributions from the 10th IEEE International Conference on Intelligent Data Acquisition and Advanced Computing Systems: Technology and Applications (IDAACS’2019), Metz, France, as well as external contributions.